Tinjauan Atas Penerapan Pajak Pertambahan Nilai (PPN) di PT. Indo Kuantum Logistik - Tasya Aulia Rahman Hartomo (2021)
Tax is a form of participation of individuals or entities to the state that is coercive and comes from the law and does not receive direct compensation or payment and is used for state purposes. As with the economy in a family, the country's economy also recognizes sources of income and expenditure. Taxes are also the main source of state revenue. PT. Indo Kuantum Logistik is a company engaged in transportation and logistics (goods procurement services). In its activities, PT Indo Kuantum Logistik utilizes Value Added Tax (PPN) and acts as a collector based on Laws and Government Regulations. in the current year has an obligation to collect, deposit, and report taxes payable every month or during the tax period. The application of Value Added Tax at PT Indo Kuantum Logistik is in fact different in each of the services it provides, such as Trucking services which charge 10% for VAT and Forwarding services are subject to an effective tariff of 1%. The purpose of this Final Project report is to learn more about the implementation of withholding, depositing and reporting Value Added Tax (VAT) and also knowing the procedures for making tax invoices and filling out electronic SPT using the E-Tax Invoice application. Collection, Deposit and Reporting of Value Added Tax for freight forwarding services of PT. Indo Kuantum Logistik complies with applicable tax regulations, namely the limit for Depositing and Reporting Value Added Tax is at the end of each month in the following month.